Two decades of declining poverty but rising inequality in Laos - Peter George Warr; Sitthiroth Rasphone; Jayant Menon (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2018)
Over the past two decades consumption inequality has risen within Laos, while absolute poverty incidence halved. The estimated Gini coefficient of private household expenditures per person rose from 0.311 to 0.364. This increase in the sample-based estimate of inequality was statistically significant and occurred in all regions, in both rural and urban areas and among all major ethnic, educational and sectoral employment categories. Within-group increases in inequality dominated between-group changes, but official policy largely overlooks this point, focusing on reducing inequality between, rather than within major groups. This assessment argues that economic inequality should become a more pressing policy concern.
Keywords: D31; D39; I39; 330; Expenditure inequality; poverty reduction; Gini coefficient; Laos